Cross‐cultural comparisons between the earthquake preparedness models of Taiwan and New Zealand. Issue 2 (17th August 2015) - Jang, Li‐Ju; Wang, Jieh‐Jiuh; Paton, Douglas; Tsai, Ning‐Yu
Abstract : Taiwan and New Zealand are both located in the Pacific Rim where 81 per cent of the world's largest earthquakes occur. Effective programmes for increasing people's preparedness for these hazards are essential. This paper tests the applicability of the community engagement theory of hazard preparedness in two distinct cultural contexts. Structural equation modelling analysis provides support for this theory. The paper suggests that the close fit between theory and data that is achieved by excluding trust supports the theoretical prediction that familiarity with a hazard negates the need to trust external sources. The results demonstrate that the hazard preparedness theory is applicable to communities that have previously experienced earthquakes and are therefore familiar with the associated hazards and the need for earthquake preparedness. The paper also argues that cross‐cultural comparisons provide opportunities for collaborative research and learning as well as access to a wider range of potential earthquake risk management strategies.